Electrical Energy Storage Devices for Active Buildings - Rajabinezhad, Mohamad Amin; Firoozi, Hooman; Khajeh, Hosna; Laaksonen, Hannu (Springer, 2022)
The structure of traditional power systems is changing from passive to active due to the increased amount of renewable energy sources as well as the presence of microgrids, energy communities, active buildings, and active network management. Due to the stochastic nature of renewable energy sources, their intermittent output power can create stability issues within different levels of electrical systems. Therefore, as a potential solution, the integration of energy storage systems in different sizes/scales has become pivotal. In this chapter, different types of energy storage devices along with their applications and capabilities are discussed. The focus of this chapter is mostly on electrical and electrochemical energy storage that could be utilized in active buildings. These devices are categorized as static storages as well as mobile storages such as electric vehicles. The technologies, requirements, as well as the application of mentioned storages are presented in this chapter as well.
Keywords: Active buildings; Battery energy storage; Battery storage system; Community energy storage system; Demand-side storage systems; Electric vehicles; Electrical energy storage; Electrical storage; Electrochemical energy storage; Energy flexibility; Energy storage; Energy storage devices; Energy storage system; Flexible energy resources; Flexible energy storage; Microgrid energy storage system; Static energy storage; fi=Sähkötekniikka|en=Electrical Engineering|